Preparation and Photocatalytic Activity of Ag Modified Ti-Doped-Bi2O3 Photocatalyst. (17th February 2014) - Zhang, Lilan; Niu, Junfeng; Li, Duo; Gao, Ding; Shi, Jianghong
Abstract : Ti doped Bi2 O3 (TDB) and Ag ion modified Ti doped Bi2 O3 (Ag@TDB) photocatalysts were prepared by framework replacement synthesis method with different Ag loadings (0.05, 0.3, 0.75, and 1.0 mol/L AgNO3 ). The structural properties of the prepared catalysts were studied by scanning electron microscope (SEM), X-ray diffraction (XRD), BET surface area, and UV/Vis diffuse reflectance (DRS). The XRD spectra of the Ti doped Bi2 O3 calcined at 650°C showed the diffraction peaks of a mixture of Bi12 TiO20 and Bi4 Ti3 O12, with bits of mixed crystallite consisting of TiO2 and B2 O3 . A high blue shift in the range 650–550 nm was detected in the DRS band. This blue shift increased with the decreasing Ag content. The photocatalytic activities of the catalysts were evaluated for the degradation of crystal violet (CV) under UV light irradiation. The results indicated that the degradation rate of CV by using 1.0 mol/L AgNO3 doped bismuth titanate composite photocatalyst (1.0 Ag@TDB) was 1.9 times higher than that by using the bare Ti doped Bi2 O3 photocatalyst. The higher activity of Ag@TDB is due to the enhancement of electron-hole pair separation by the electron trapping of silver particles.